Proceedings of the Sixteenth ACM Symposium on Operating Systems Principles 1997
DOI: 10.1145/268998.266700
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of log-structured file systems with adaptive methods

Abstract: File system designers today face a dilemma. A log-structured file system (LFS) can offer superior performance for many common workloads such as those with frequent small writes, read traffic that is predominantly absorbed by the cache, and sufficient idle time to clean the log. However, an LFS has poor performance for other workloads, such as random updates to a full disk with little idle time to clean. In this paper, we show how adaptive algorithms can be used to enable LFS to provide high performance across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Since its inception, LFS has been evaluated [3,27,35,38] and used [1,7,12,17] by many different groups. Much of the work done to improve both LFS and LFS cleaners is directly applicable to CVFS.…”
Section: Related Workmentioning
confidence: 99%
“…Since its inception, LFS has been evaluated [3,27,35,38] and used [1,7,12,17] by many different groups. Much of the work done to improve both LFS and LFS cleaners is directly applicable to CVFS.…”
Section: Related Workmentioning
confidence: 99%
“…Matthews et al demonstrated how to overcome the segment cleaning problem at higher disk utilizations [6]. They present an adaptive cleaning mechanism that chooses either full segment cleaning, as in LFS, or their technique of hole-plugging.…”
Section: A Log-structured File Systems and Their Successorsmentioning
confidence: 99%
“…It offers bad performance if there are random writes, high utilization, and little idle time. Matthews et al [1997] investigate three techniques to improve the write performance of an LFS and one technique to improve the read performance. A simulation predicts the results of using the techniques.…”
Section: Cleaning (Reclamation Of Space) In a Log-structured File Systemmentioning
confidence: 99%